A Burkholderia pseudomallei Colony Variant Necessary for Gastric Colonization - C. R. Austin (American Society for Microbiology, 2015)
ABSTRACT  Diverse colony morphologies are a hallmark of Burkholderia pseudomallei recovered from infected patients. We observed that stresses that inhibit aerobic respiration shifted populations of B. pseudomallei from the canonical white colony morphotype toward two distinct, reversible, yet relatively stable yellow colony variants (YA and YB). As accumulating evidence supports the importance of B. pseudomallei enteric infection and gastric colonization, we tested the response of yellow variants to hypoxia, acidity, and stomach colonization. Yellow variants exhibited a competitive advantage under hypoxic and acidic conditions and alkalized culture media. The YB variant, although highly attenuated in acute virulence, was the only form capable of colonization and persistence in the murine stomach. The accumulation of extracellular DNA (eDNA) was a characteristic of YB as observed by 4′,6-diamidino-2-phenylindole (DAPI) staining of gastric tissues, as well as in an in vitro stomach model where large amounts of eDNA were produced without cell lysis. Transposon mutagenesis identified a transcriptional regulator (BPSL1887, designated YelR) that when overexpressed produced the yellow phenotype. Deletion of yelR blocked a shift from white to the yellow forms. These data demonstrate that YB is a unique B. pseudomallei pathovariant controlled by YelR that is specifically adapted to the harsh gastric environment and necessary for persistent stomach colonization. IMPORTANCE  Seemingly uniform populations of bacteria often contain subpopulations that are genetically identical but display unique characteristics which offer advantages when the population is faced with infrequent but predictable stresses. The pathogen Burkholderia pseudomallei is capable of forming several reversible colony types, and it interconverted between one white type and two yellow types under certain environmental stresses. The two yellow forms exhibited distinct advantages in low-oxygen and acidic environments. One yellow colony variant was the only form capable of chronic stomach colonization. Areas of gastric infection were marked by bacteria encased in a DNA matrix, and the yellow forms were able to produce large amounts of extracellular DNA in vitro. We also identified the regulator in control of yellow colony variant formation. These findings demonstrate a role in infection for colony variation and provide a mechanism for chronic stomach colonization—a frequently overlooked niche in melioidosis.